Aggregate stability in soils cultivated with eucalyptus - Avanzi,Junior Cesar (2011)
The objective of this work was to evaluate the aggregate stability of tropical soils under eucalyptus plantation and native vegetation, and assess the relationships between aggregate stability and some soil chemical and physical properties. Argisols, Cambisol, Latosols and Plinthosol within three eucalyptus-cultivated regions, in the states of Espírito Santo, Rio Grande do Sul and Minas Gerais, Brazil, were studied. For each region, soils under native vegetation were compared to those under minimum tillage with eucalyptus cultivation. The aggregate stability was measured using the high-energy moisture characteristic (HEMC) technique, i.e., the moisture release curve at very low suctions. This method compares the resistance of aggregates to slaking on a relative scale from zero to one. Thus, the aggregate stability from different soils and management practices can be directly compared. The aggregate stability ratio was greater than 50% for all soils, which shows that the aggregate stability index is high, both in eucalyptus and native vegetation areas. This suggests that soil management adopted for eucalyptus cultivation does not substantially modify this property. In these soils, the aggregate stability ratio does not show a good relationship with clay or soil organic matter contents. However, soil organic matter shows a positive relationship with clay content and cation exchange capacity.